WEED CONTROL UNDERSTORY WEED MANAGEMENT IN COCONUT LANDS - L. V. K. LIYANAGE; M. DE. S. LIYANAGE (International Coconut Community Journal, 1992)
Coconut (Cocos nucifera L.) is by far the most extensively cultivated plantation crop in Sri Lanka. It is essentially a small holder crop comprising about 86% of small. holdings and homesteads and the balance belonging to the estate sector. The growth habit of the palm and its canopy structure requires a wide, spacing between palms, which permits abundant sunlight to the understory. As a result, the unutilised space beneath the plantation becomes invaded by a wide range of perennial and annual weed species. Such weeds invariably compete with coconut for soil moisture and nutrients, affecting its growth and yield and obstructing routine estate practices. Management of the understory weed growth is, therefore, considered an essential step in maintaining the plantation. In fact, the cost of weeding accounts for a substantial proportion of the total recurrent expenditure for maintenance.